Cinemachines : an essay on media and method - Stewart, Garrett (Chicago : The University of Chicago Press, 2019)
"This book explores the cultural and mechanical contrivances that subtend the modernist invention and practice of cinema. This book ponders the place of authorial intention in making a movie: how and when does the author break through the technical/narrative framework that defines what movies are and can do. Important films and filmmakers are discussed"--
Prelude: Advance Press -- Sneak Preview: Past the Apparatus? -- Production Notes: Tech Specs -- Featurette: The Making of a Medium -- Rerun Triple Bill: Kinks of Comedy -- VFX Festival: SF and Beyond -- Omnibus Review: On the Technopoetics of CGI -- PostScript: Special AffX
eBooks on EBSCOhost
Keywords: Cinematography; Digital cinematography; Motion pictures; Cinéma.; Cinéma numérique.; cinematography; Motion pictures; Cinematography; Digital cinematography